2009
DOI: 10.1159/000209334
|View full text |Cite
|
Sign up to set email alerts
|

The Role of UFT in Metastatic Colorectal Cancer

Abstract: 5-Fluorouracil (5-FU) has been the most widely used chemotherapeutic agent for metastatic colorectal cancer (mCRC) and 5-FU combination therapy improves efficacy compared with monotherapy. The oral fluoropyrimidine UFT (tegafur-uracil) with leucovorin (LV) improves tolerability and has replaced 5-FU in many regimens. The efficacy and tolerability of UFT with LV in the first-line treatment of mCRC has been demonstrated in a number of phase II studies. In two phase III studies, UFT with LV has been shown to have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 94 publications
0
15
0
Order By: Relevance
“…38 The rationale for adopting UFT in the present study was the comparable clinical efficacy data with (the now more commonly used) capecitabine but with a better tolerability profile. [39][40][41] The incidence of palmar-plantar erythema was low; however, we acknowledge that this agent is no longer in routine use, and future studies will need to incorporate an alternative 5-FU as a backbone of the therapy. Our CTC data confirmed that enumeration of CTCs at baseline is prognostic for OS in patients with ACRC, consistent with data from previous reports.…”
Section: Context Of Other Datamentioning
confidence: 99%
“…38 The rationale for adopting UFT in the present study was the comparable clinical efficacy data with (the now more commonly used) capecitabine but with a better tolerability profile. [39][40][41] The incidence of palmar-plantar erythema was low; however, we acknowledge that this agent is no longer in routine use, and future studies will need to incorporate an alternative 5-FU as a backbone of the therapy. Our CTC data confirmed that enumeration of CTCs at baseline is prognostic for OS in patients with ACRC, consistent with data from previous reports.…”
Section: Context Of Other Datamentioning
confidence: 99%
“…However, the protracted venous infusion of 5-FU requires in-dwelling catheters and outpatient ambulatory infusion pumps that are associated with potential risks of infection and thrombosis and are inconvenient for the patients. Consequently, oral fluoropyrimidines, such as S-1, UFT and capecitabine, have been developed as a therapeutic alternative to the protracted venous infusion of 5-FU [6,7,8]. …”
Section: Introductionmentioning
confidence: 99%
“…Continuous infusion avoided the high serum 5‐FU levels that could be observed with bolus injection dosage and may be efficacious in CRC without increasing anastomotic leakage. The oral fluoropyrimidine drug, capecitabine, evolved to ameliorate patient convenience and tolerability and has replaced continuous infusions of 5‐FU in many chemotherapy regimens 33. Capecitabine appears to be a promising substitute to continuous infusions of 5‐FU, and pharmacokinetic researchers have reported that successive oral administration provided a steady‐state 5‐FU concentration that was comparable with that achieved by a 5 day continuous infusion 34, 35.…”
Section: Discussionmentioning
confidence: 99%